Sensory Characteristics and Hedonic Preferences of Sprinkle Chili Sauce with Variations in Kecombrang Proportion - Ulima Putri Nabilah; Mauren Gita Miranti; Hidayatun Musyasyaroh; Diwyacitta Antya Putri (Universitas Negeri Padang, 2026)
Sprinkle chili sauce represents a contemporary chili powder-derived product that has experienced growing consumer interest as a seasoning agent used to intensify the flavor profile of various dry food preparations. The present study was undertaken to examine the hedonic properties of dried kecombrang sprinkle chili sauce, establish the optimal product formulation, and characterize the selected formula across varying proportions of kecombrang incorporation. A quantitative descriptive experimental approach was adopted, encompassing six distinct treatment levels of kecombrang concentration, specifically 50%, 60%, 70%, 80%, 90%, and 100%. Sensory evaluation was carried out involving 35 semi-trained panelists with a culinary arts background, who assessed each product formulation against five sensory attributes: color, aroma, texture, taste, and overall acceptability. Statistical analysis was performed using One Way Analysis of Variance (ANOVA), subsequently followed by the Duncan Multiple Range Test (DMRT) to identify significant differences among treatments and determine the most preferred formulation. Findings revealed that variations in kecombrang proportion exerted a statistically significant influence on the hedonic quality of the dried kecombrang sprinkle chili sauce across all evaluated attributes. Among the six formulations tested, F1 (50% kecombrang) emerged as the most favorable treatment, exhibiting a well-balanced reddish-brown appearance, a characteristic yet subtle kecombrang aroma, and a dry texture with a moderately fine consistency that aligned most closely with panelist preferences.